2022
DOI: 10.3390/jcm11216491
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Angiogenic and Inflammatory Cytokines in Multiple Myeloma: Role in Plasma Cell Clonal Expansion and Drug Resistance

Abstract: Multiple myeloma (MM) is the second most common hematological malignancy, and despite the introduction of innovative therapies, remains an incurable disease. Identifying early and minimally or non-invasive biomarkers for predicting clinical outcomes and therapeutic responses is an active field of investigation. Malignant plasma cells (PCs) reside in the bone marrow (BM) microenvironment (BMME) which comprises cells (e.g., tumour, immune, stromal cells), components of the extracellular matrix (ECM) and vesicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 156 publications
1
7
0
Order By: Relevance
“…The presented cases by us and others ( 3 , 4 , 12 , 19 21 ) support the use of JAK-inhibitors as an effective targeted therapy for patients with SPENCDI and severe cytopenias. Lack of effective biomarkers to capture the clinical response to JAK-inhibitors (e.g.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The presented cases by us and others ( 3 , 4 , 12 , 19 21 ) support the use of JAK-inhibitors as an effective targeted therapy for patients with SPENCDI and severe cytopenias. Lack of effective biomarkers to capture the clinical response to JAK-inhibitors (e.g.…”
Section: Discussionsupporting
confidence: 63%
“…Both parents were identified as heterozygous asymptomatic carriers of one of the variants ( Figures 2B, C ; Supplementary Materials ; Supplementary Table 1 ). Based on the favorable therapeutic response of other patients with type I interferonopathies to JAK inhibitors ( 3 , 4 , 12 , 19 21 ), and the shared pathophysiologic hallmarks of SPENCDI with other type I interferonopathies ( 14 , 22 ), a therapeutic trial with the JAK1/JAK2 inhibitor ruxolitinib was initiated (0.4 mg/kg/day). Within a week from initiation of therapy, the patient reported significantly improved energy levels.…”
Section: Resultsmentioning
confidence: 99%
“…During the transition from the avascular to the vascular phase, the activation of oncogenes such as c-myc, c-fos, c-jun, and Jun-B induces MM cells to secrete high amounts of pro-angiogenic cytokines, including vascular endothelial growth factor (VEGF), fibroblast growth factor 2 (FGF-2), hepatocyte growth factor (HGF), angiopoietin-1, and insulin-like growth factor 1 (IGF-1) [ 13 , 14 , 15 ]. In turn, these cytokines act on BMSCs and on MM cells as well.…”
Section: Angiogenesis and Vasculogenesis In Multiple Myelomamentioning
confidence: 99%
“…In detail, IL-1β regulates the transcription of IL-6, which is mediated by upregulation of NF-kB activation. IL-6 stimulates the proliferation-inducing ligand ( APRIL ) and B-cell activating factor (BAFF) production, activating NF-kB/PI3K/AKT and MAPK pathways and thus promoting MM cell survival [ 62 ]. TNF-α also induces IL-6 secretion in BMSCs activating NF-kB [ 62 ].…”
Section: Distinctive Features Of Mscs In Multiple Myelomamentioning
confidence: 99%
“…IL-6 stimulates the proliferation-inducing ligand ( APRIL ) and B-cell activating factor (BAFF) production, activating NF-kB/PI3K/AKT and MAPK pathways and thus promoting MM cell survival [ 62 ]. TNF-α also induces IL-6 secretion in BMSCs activating NF-kB [ 62 ]. Lust et al demonstrated both in vivo and in vitro that blockade of IL-1β results in decreased IL-6 activity [ 63 , 64 ].…”
Section: Distinctive Features Of Mscs In Multiple Myelomamentioning
confidence: 99%